Aleochara (Calochara) hongi Ahn & Jung (Coleoptera: Staphylinidae: Aleocharine), a new species from animal feces with a discussion of its phylogenetic relationships - Ahn, Kee-Jeong; Jung, Jong-Keun (Zootaxa, 2025)
A systematic study of the Aleochara Gravenhorst Calochara Casey using morphological and molecular characters is presented. As a result of a taxonomic study of the subgenus in Korea, we found a new species from animal feces [Aleochara (Calochara) hongi Ahn & Jung, new species]. The subgenus Calochara Casey is new to the East Asian fauna, and its phylogenetic relationships are discussed using partial COI and COII sequences. Diagnoses and illustrations of the habitus photographs, median lobe, and spermatheca are provided to facilitate identification.